2017
DOI: 10.1080/17567505.2017.1317071
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Adapting to Climate Change: Challenges for the Historic Environment

Abstract: historic england, The engine house, swindon, UK ABSTRACT Our changing climate poses risks to the historic environment but also brings opportunities for new discoveries and ways for people to engage with it. At Historic England, part of our responsibility is to understand what future changes we might expect and the impact these may have on our ability to protect historic buildings, archaeological remains and landscapes. This paper describes projects that have used spatial analysis to assess the risk and vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Examples of the latter include improving the monitoring, maintenance, and preparedness to floods and landslides at cultural heritage sites [1,16]. Heathcote et al [17] described the adaptive measures suggested in the Historic England climate change adaptation plan to cope with the impacts of climate change on cultural heritage in England, for example, developing approaches to deal with change and loss. Haugen and Mattson [18] investigated the impacts of climate change on cultural heritage in Norway, and recommended adaptive measures to deal with the risks identified.…”
Section: Adapting Cultural Heritage To Climate Change Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the latter include improving the monitoring, maintenance, and preparedness to floods and landslides at cultural heritage sites [1,16]. Heathcote et al [17] described the adaptive measures suggested in the Historic England climate change adaptation plan to cope with the impacts of climate change on cultural heritage in England, for example, developing approaches to deal with change and loss. Haugen and Mattson [18] investigated the impacts of climate change on cultural heritage in Norway, and recommended adaptive measures to deal with the risks identified.…”
Section: Adapting Cultural Heritage To Climate Change Risksmentioning
confidence: 99%
“…Efforts in the area of adaptation are yet limited to the dissemination of guidelines and recommendations for implementing adaptation measures [1,[16][17][18][19][20][21][22][23][24][25], the identification of the determinants of adaptive capacity [26], and the identification of the barriers to adaptation [27][28][29][30]. Sabbioni et al [1,16] developed guidelines for adapting the European cultural heritage to climate change impacts, which were later adopted by the Italian Strategic Agenda [31,32].…”
Section: Adapting Cultural Heritage To Climate Change Risksmentioning
confidence: 99%
“…Within the context of cultural heritage adaptation, Heathcote et al [20] described two types of adaptation strategies. The first is a set of low-risk strategies that focus on improving protection from changing climate conditions that are already happening, such as regular maintenance to ensure historic buildings are weather-proof.…”
Section: Introductionmentioning
confidence: 99%
“…Research accomplished to date on adapting our cultural heritage to climate change centres on the dissemination of guidelines and recommendations to implement adaptation measures (Sabbioni et al, 2010, Sabbioni et al, 2008, Heathcote et al, 2017, Haugen and Mattsson, 2011, Cassar, 2016, Pollard-Belsheim et al, 2014, Carmichael et al, 2017a, Fatorić and Seekamp, 2017a, Grøntoft, 2011, Hall, 2015 and on the identification of opportunities and barriers to adaptation (Phillips, 2014, Fatorić and Seekamp, 2017b, Carmichael et al, 2017b, Casey, 2018, Sesana et al, 2018. Preserving cultural heritage from the impacts of climate change requires a shift from reactive to proactive adaptation (Sesana et al, 2018).…”
Section: Cultural Heritage and Climate Changementioning
confidence: 99%